Perkembangan Lobi Yahudi dan Pengaruhnya terhadap Politik Luar Negeri dan Kongres Amerika Serikat - Setiawan, Agus (Wacana, Journal of the Humanities of Indonesia, 2004)
United States' foreign policy has been extremely influenced by some determinant factors both personal and institutional. However, by the end of World War II, an institution known as interest group, played important role relatively to the determination of United States' foreign policies, particularly those which were related to Middle East conflict. A Jewish lobby known as AIPAC (American Israeli Public Affairs Committee) has been the most powerful interest group to influence the United States' foreign policy especially after President Truman's administration. This article describes the internal development of AIPAC and some AIPAC's actions in order to get public supports to influence the decision makers.